Jalan Tuhan dan Kemanusiaan dalam Pendidikan - Mulkhan, Abdul Munir (Yayasan Sukma, 2017)
One’s faith and personality are produced during his life experience in dialogue with himself, dialogue with the nature, and dialogue with the socio-cultural environment in which he lives, grows and develops. Meanwhile, education is a planned, programmed attempt to engineer this experience of life to obtain maximum results for the future life. Education is necessarily comprehensive and synthetic. The loss of an element in education can be the cause of personality imbalances as is now the case in the reality of life in this country: motorcycle gangs, brawls between villages, corruption, and accusing of one another as infidel. Therefore, education process must be humanist or ngewongke and that being virtuous is the endless process of becoming.[Keimanan atau kebertuhanan dan kepribadian seseorang adalah produk pengalaman hidupnya dalam berdialog dengan dirinya sendiri, berdialog dengan alam, dan berdialog dengan lingkungan sosial-budaya tempat ia hidup, tumbuh dan berkembang. Sementara itu, pendidikan merupakan rekayasa pengalaman hidup tersebut secara terencana dan terprogram guna memperoleh hasil maksimal bagi kepentingan masa depan sejarah umat manusia. Pendidikan secara niscaya bersifat komprehensif sekaligus sintetis. Hilangnya satu unsur dalam pendidikan bisa menjadi penyebab ketimpangan kepribadian seperti yang kini banyak terjadi dalam realitas kehidupan di negeri ini: geng motor, tawuran antardesa, korupsi, dan pengkafiran satu atas yang lain. Karena itu, pendidikan mesti humanis atau ngewongke dan bahwa menjadi saleh adalah proses menjadi tanpa akhir.]